Respuesta :
Hello,
1)
3x²y²-2xy²-8y²=y²(3x²-2x-8)
=y²(3x²-6x+4x-8)
=y²(3x(x-2)+4(x-2))
=y²(x-2)(3x+4)
2)
x²-36=x²-6²=(x+6)(x-6)
1)
3x²y²-2xy²-8y²=y²(3x²-2x-8)
=y²(3x²-6x+4x-8)
=y²(3x(x-2)+4(x-2))
=y²(x-2)(3x+4)
2)
x²-36=x²-6²=(x+6)(x-6)
Answer:
Check below.
Step-by-step explanation:
Part A:
we have three terms:
[tex]3x^2y^2-2xy^2-8y^2[/tex].
As all terms have [tex]y^2[/tex] we can factor the [tex]y^2[/tex]
[tex]3x^2y^2-2xy^2-8y^2= y^2(3x^2-2x-8)[/tex].
Part B:
we have a trinomial
[tex]x^2+10x+25[/tex]
As all terms are positive, we can factor it by searching two numbers that multiplied are 25 and added are 10, those are 5 and 5:
[tex]x^2+10x+25= (x+5)(x+5) = (x+5)^2.[/tex]
Part C:
We have a binomial:
[tex]x^2-36[/tex]
as both terms have square root, we can apply difference of perfect squares. That is, two factors with the roots, one with -6 and the other with 6:
[tex]x^2-36=(x-6)(x+6).[/tex]